Evaluation on properties of tender mixes - Abd. Rahman, Zanariah (2006)
Tender mix has caused many problems to the contractor during the construction of hot mix asphalt (HMA) pavement. The objective of this paper was to investigate the properties of tender mixes as related to the problem of rutting. Two mixes of ACW20 were designed in compliance to Jabatan Kerja Raya (JKR) specification. One mix was designed with typical dense graded gradation but away from the maximum density line (MDL) described as control mix. The other mix was designed close to MDL to simulate tender mix. Marshall sample were prepared in order to determine the optimum bitumen content (OBC) and volumetric properties of compacted mixtures. Using the OBC obtained from Marshall samples, two beams were fabricated for each mix for the wheel-tracking test. Comparisons of rut depth between control mix and tender mix were made at 500, 1000, 2000 and 5000 passes. Volumetric properties results indicate that ‘tender mix’ is not tender as expected due to high voids in the mineral aggregate (VMA) compared to control mix. However, there is a significant difference between tender mix and control mix in terms of rutting according to the t-Test statistical analysis. Furthermore, tender mix indicated low stability and stiffness value which show that the gradation of tender mix that was designed close to MDL are recommended as poor gradation and show a potential problem in mixes if the mix is used